2018
DOI: 10.1038/s41467-018-04656-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive tail anchorage determines velocity and force produced by kinesin-14 between crosslinked microtubules

Abstract: Form and function of the mitotic spindle depend on motor proteins that crosslink microtubules and move them relative to each other. Among these are kinesin-14s, such as Ncd, which interact with one microtubule via their non-processive motor domains and with another via their diffusive tail domains, the latter allowing the protein to slip along the microtubule surface. Little is known about the influence of the tail domains on the protein’s performance. Here, we show that diffusive anchorage of Ncd’s tail domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…This can be made possible by extending our assay to enable torque measurements, for example by using 3D optical tweezers 13 . In a recent study 25 it was shown that Ncd motors can only generate sub-pN forces along the longitudinal axis of the microtubule due to their diffusive tail anchorage. However, it is conceivable that in the axial direction the diffusivity of the Ncd tails is limited (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be made possible by extending our assay to enable torque measurements, for example by using 3D optical tweezers 13 . In a recent study 25 it was shown that Ncd motors can only generate sub-pN forces along the longitudinal axis of the microtubule due to their diffusive tail anchorage. However, it is conceivable that in the axial direction the diffusivity of the Ncd tails is limited (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most experiments were performed with recombinant His6-tagged Drosophila Melanogaster full length GFP-Ncd expressed in SF9 insect cells and purified after cleavage of the His6-tag, as described previously 25 . For FLIC-based sliding motility assays, a different batch of full length GFP-Ncd expressed in Escherichia coli and purified as described previously (His6-tag not cleaved) 10 was used.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Noteworthy, the kinesin-14 family members Ncd and HSET, in addition to a motor head, contain a diffusible tail [2], making them able to form asymmetric connections with motor and diffusible head bound to different microtubules. Interestingly, Kinesin-14 can only reach sub-picoNewton forces when crosslinking antiparallel microtubules [10], even though its motor domain is able to exert picoNewton forces in vitro. This suggests that the diffusible tail of kinesin-14 limits the force exerted by its motor domain.…”
Section: Introductionmentioning
confidence: 99%
“…It was realised in vitro using PRC1 and kinesin-5 [20]. System C corresponds to experiments using Kinesin-14 [10], in which the sliding is produced by motors composed of a diffusible tail and a motor head, without crosslinkers. Finally, in system D, diffusible motors pull against diffusible crosslinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Kinesin-14s, such as Ncd, interconnect with one MT through their non-processive motor domains and with additional MT through their tail domains which permit the protein to slide alongside the MT surface. Previous data indicates the character of kinesin-14 as a flexible element involved in sliding and crosslinking MT to enable mitotic spindle remodeling(Lüdecke, Seidel, Braun, Lansky & Diez, 2018). Miro, small GTPase, targets peroxisomes and regulates MT-dependent peroxisome motility.…”
mentioning
confidence: 99%